David Rittenhouse - Hindle, Brooke (Princeton legacy library., 2017)
One of the great figures of the American Enlightenment, David Rittenhouse of Pennsylvania rose from his work as a mechanic and clockmaker of exquisite craftsmanship to informed, careful astronomy and effective experimental work in optics, magnetism, and psychology. This book shows how he applied his scientific ability to public projects and, eventually, to the establishment of a 'national mint', and how he used his increasing prestige to further crucial political objectives of the time. This man, considered a brilliant scientist by Franklin and Jefferson, was, according to Benjamin Rush, "one of the luminaries of the eighteenth century."Originally published in 1964. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.